The effects of aging on hepatic microsomal scaling factor and hepatocellularity number in the horse. (2nd December 2018) - Shibany, Khaled A.; Tötemeyer, Sabine; Pratt, Stefanie L.; Paine, Stuart W.
Abstract: 1. Scaling factor values for the in vitro - in vivo extrapolation of hepatic metabolic clearance for xenobiotics have not yet been determined in horses. Scaling factors were determined by comparing the total protein and or cytochrome (CYP) P450 content in microsomes and cryopreserved hepatocytes against the content in the liver. 2. Microsomal protein per gram of liver (MPPGL) and hepatocellularity number per gram of liver (HPGL) using CYP P450 content method ranged 41–73 mg/gram of liver (mean= 57 mg/gram of liver, n = 39) and 146–320 × 10 6 cells/g of liver (mean = 227× 10 6 cells/g of liver, n = 18), respectively and 156–352 × 10 6 cells/g of liver (mean = 232× 10 6 cells/g of liver) using total protein method. 3. A non-monotonic and inverse relationship between age and MPPGL and HPGL, respectively, was observed. Between one and 20 y of age, the liver cell size decreases as age increases. Subsequently, the cell size increases until the hepatocytes of the oldest horses approached the size found in the youngest horses. Hepatocyte density was inversely related to the size of the hepatocytes. 4. This study provides the first extensive and comprehensive data demonstrating the relationship between the size of hepatocytes and HPGL in any species.